EDUKASI LITERASI KEMASAN PUPUK PADA KELOMPOK TANI DI JORONG SUNGAI AUR, KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Jamilah Munir; Syahrial Syahrial; Yulia Rahmawati (Jurnal Abdi Insani, 2022)
The importance of knowing literacy on fertilizer packaging will give farmers the ability to examine fertilizers, their contents, and their intended use. Many problems occur in farming communities in Indonesia, it turns out that they are not able to understand the literacy that appears on the packaging of artificial fertilizers sold at fertilizer grocery. The cultivated center of corn r in West Pasaman is more focused on Sungai Aur District. Objective; to provide literacy education on the packaging of artificial fertilizers sold at fertilizer grocery in Sungai Aur District, West Pasaman Regency. The service activity began with a socialization event about the program of activities to be carried out, then a questionnaire was circulated to find out the understanding of literacy in the packaging of artificial fertilizers sold at fertilizer grocery. The participants consisted of 3 farmer groups including; The Mekar Abadi Farmers Group, then Harapan Sejahtera, and Karya Makmur, the number of participants was 25 people, the activity was carried out at the Mekar Abadi Farmer group's residence in May 2022. The socialization event was carried out starting by sending letters to agricultural extension groups in the area. Furthermore, the head of the farmer group and its members were invited to attend the event. From the results of the activity, it is known that the literacy understanding of farmers' fertilizer packaging was still low so farmers use fertilizers that are not optimal and efficient. In general, farmers did not get a good understanding of how to apply fertilizer, the right dose and dose are given to plants. Farmers also did not know and recognize illegal and fake fertilizers.